Predictors of graft survival at diagnosis of antibody‐mediated renal allograft rejection: a retrospective single‐center cohort study. (15th October 2019) - Waiser, Johannes; Klotsche, Jens; Lachmann, Nils; Wu, Kaiyin; Rudolph, Birgit; Halleck, Fabian; Liefeldt, Lutz; Bachmann, Friederike; Budde, Klemens; Duerr, Michael
Summary: Antibody‐mediated rejection (ABMR) is a major cause of graft loss in renal transplantation. We assessed the predictive value of clinical, pathological, and immunological parameters at diagnosis for graft survival. We investigated 54 consecutive patients with biopsy‐proven ABMR. Patients were treated according to our current standard regimen followed by triple maintenance immunosuppression. Patient characteristics, renal function, and HLA antibody status at diagnosis, baseline biopsy results, and immunosuppressive treatment were recorded. The risk of graft loss at 24 months after diagnosis and the eGFR slope were assessed. Multivariate analysis showed that eGFR at diagnosis and chronic glomerulopathy independently predict graft loss (HR 0.94; P  = 0.018 and HR 1.57; P  = 0.045) and eGFR slope (beta 0.46; P  < 0.001 and beta −5.47; P  < 0.001). Cyclophosphamide treatment (6× 15 mg/m 2 ) plus high‐dose intravenous immunoglobulins (IVIG) (1.5 g/kg) was superior compared with single‐dose rituximab (1× 500 mg) plus low‐dose IVIG (30 g) (HR 0.10; P  = 0.008 and beta 10.70; P  = 0.017) and one cycle of bortezomib (4× 1.3 mg/m 2 ) plus low‐dose IVIG (HR 0.16; P  = 0.049 and beta 11.21; P  = 0.010) regarding the risk of graft loss and the eGFR slope. In conclusion, renal function at diagnosis and histopathological signs of chronic ABMR seem to predict graft survival independent of the applied treatment regimen. Stepwise modifications of the treatment regimen may help to improve outcome.